Peningkatan kompetensi motorik mahasiswa dengan pelatihan hands-on simulation dalam evakuasi pasien - Abil Rudi; Kafi Pangki Suwito (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Patient evacuation is a critical mobilization procedure in disaster management or medical emergencies. Proficiency in patient evacuation is a fundamental competency that health students must master to minimize the risk of further injury during emergency situations. Purpose: To enhance students' motor skills in performing safe and effective patient evacuation through the application of a hands-on simulation method. Method: This activity was conducted on Tuesday, May 12, 2026, from 13:00 to 16:00 WIB at the Emergency Nursing Laboratory, involving 16 health students as participants. The procedure prioritized a hands-on simulation approach featuring interactive dialogue and active group participation, covering essential evacuation topics such as patient safety principles, manual mechanical transfer techniques, and the operation of assistive devices like stretchers. Participants' motor skill competencies were measured using an observation instrument—specifically a procedural assessment checklist—evaluated before (pre-test) and after (post-test) the training, with results presented descriptively. Results: The findings indicate that prior to the training intervention (pre-test), 12 participants (75.0%) fell into the